2022
DOI: 10.1155/2022/6315648
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Algorithm for Special Action Recognition of Football

Abstract: Soccer (football) is a popular form of exercise on the planet. There are a lot of individuals who tune into football matches in real time on television or the Internet. A game of American football lasts 90 minutes, but to save time, spectators may simply want to see a few highlights. As far as we know, no such tool exists that can be used to extract intelligent highlights from a football match. In this research, we present a technique for clever editing of live football matches. Our technology allows for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…HAR has been applied in various domains, including security [3][4][5], healthcare [6][7][8], and sports [9][10][11]. Vision-based HAR systems have been employed to support quantitative evaluation and judgment in various sports [12][13][14][15][16][17][18]. However, few studies have reported the application of action recognition technology in martial arts disciplines, such as Taekwondo [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…HAR has been applied in various domains, including security [3][4][5], healthcare [6][7][8], and sports [9][10][11]. Vision-based HAR systems have been employed to support quantitative evaluation and judgment in various sports [12][13][14][15][16][17][18]. However, few studies have reported the application of action recognition technology in martial arts disciplines, such as Taekwondo [1,2].…”
Section: Introductionmentioning
confidence: 99%